2022
DOI: 10.1002/anie.202111816
|View full text |Cite
|
Sign up to set email alerts
|

Depositing Molecular Graphene Nanoribbons on Ag(111) by Electrospray Controlled Ion Beam Deposition: Self‐Assembly and On‐Surface Transformations

Abstract: The chemical processing of low-dimensional carbon nanostructures is crucial for their integration in future devices. Here we apply a new methodology in atomically precise engineering by combining multistep solution synthesis of N-doped molecular graphene nanoribbons (GNRs) with mass-selected ultra-high vacuum electrospray controlled ion beam deposition on surfaces and real-space visualisation by scanning tunnelling microscopy. We demonstrate how this method yields solely a controllable amount of single, otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 104 publications
0
12
0
1
Order By: Relevance
“…A versatile and efficient CIBD system coupled to an ESI source is presented. It is proven as a valuable tool to make a lot of species “fly”: small or simple organic molecules like the porphyrin derivative Cu-TCPP, the larger biomolecules insulin and plasmid DNA with a mass of 1.7 MDa have been soft landed, so as other molecules such as spermine, 196 ZnPC (data not shown), apoferritin ( m / z of ∼10.000 Th, see Section 4 , SI), and nanocarbons like graphene nanoribbons, 227 with no limits in sight.…”
Section: Discussionmentioning
confidence: 99%
“…A versatile and efficient CIBD system coupled to an ESI source is presented. It is proven as a valuable tool to make a lot of species “fly”: small or simple organic molecules like the porphyrin derivative Cu-TCPP, the larger biomolecules insulin and plasmid DNA with a mass of 1.7 MDa have been soft landed, so as other molecules such as spermine, 196 ZnPC (data not shown), apoferritin ( m / z of ∼10.000 Th, see Section 4 , SI), and nanocarbons like graphene nanoribbons, 227 with no limits in sight.…”
Section: Discussionmentioning
confidence: 99%
“…Perfectly flat, structurally-confined nanographenes have been produced on surfaces using self-assembly and on-surface reactions of mainly planar aromatic precursor molecules. [8][9][10][11][12] Warped precursors, such as extended rubicenes, have been used recently to open the path to defective nanographenes, [13] highly sought after for electronic applications. In another study, Fasel and coworkers observed the formation of extended homochiral honeycomb networks of a warped nanographene adsorbate and elucidated the contribution of π-π and CÀ H-π interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include graphene nanoribbons, flake‐like nanographenes as well as zigzag and holey structures. Perfectly flat, structurally‐confined nanographenes have been produced on surfaces using self‐assembly and on‐surface reactions of mainly planar aromatic precursor molecules [8–12] . Warped precursors, such as extended rubicenes, have been used recently to open the path to defective nanographenes, [13] highly sought after for electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…High-vacuum electrospray deposition (HVESD) allows transferring molecular species from solution to surfaces maintained in ultra-high-vacuum (UHV) conditions with cleanliness, allowing high-resolution scanning probe studies. HVESD is an in-line setup based on electrospray deposition, where no selection of the introduced species is necessarily performed. An advantage is the option to introduce species with a broad mass distribution from a single solution.…”
mentioning
confidence: 99%